MENINGKATKAN EFEKTIVITAS PROSES PURGING ENGINE DIESEL MENGGUNAKAN DIESEL PURGING KIT BERBASIS ARDUINO UNO DI PT ASTRA INTERNATIONAL ISUZU SALES OPERATION CABANG CIPUTAT - Nugraha, Afitro Adam; Prio Sembodo; Ajib Rosadi; Busrah (Technologic, 2024)
A diesel engine is a machine known as an internal combustion engine which uses the heat of compression to ignite fuel that has been sprayed by a nozzle into the combustion chamber. The problem that often occurs in Diesel engines is interference with the fuel system. When these disturbances occur, trouble shooting must be carried out on the fuel system and periodic maintenance can be carried out to minimize disturbances to the Diesel engine fuel system. The Arduino Uno-based Diesel purging kit is equipped with digital parameters to read the turbidity level of the purging liquid so that it is expected to facilitate mechanics in the Diesel engine purging process and make it more efficient and effective. The test results show a graphic of turbidity during the first 5 minutes to 20 minutes there is a significant increase in the percentage of liquid turbidity. However, in the last minute of the process there was only an increase of 2% which means that the maximum result of the process touched the turbidity rate of 72%. After the procurement of the tool, the Diesel engine purging process cut the time by 30 minutes compared to before the tool was available